Centering disability in digital health: perspectives and actionable approaches to accessibility - Hilary Touchett; Kelley Arredondo; Stephanie C. Day; Brenda Salgado; Katherine Bay; Jan Lindsay; Felicia Skelton (Frontiers in Digital Health, 2026)
Digital health innovations hold enormous potential to expand access to care. Yet individuals with disabilities often face inequities due to systemic, environmental, and design-related barriers that limit full participation in digital health ecosystems. These challenges often arise from the ways digital tools and systems are designed rather than the impairment itself. This perspective discusses the intersection of disability, digital health, and equitable access through key disability frameworks including the International Classification of Functioning (ICF), the Health Equity Framework for People with Disabilities, and other prominent medical and biopsychosocial models. We assert that equitable digital health for people with disabilities requires a shift toward accessibility-as-standard, grounded in Universal Design, participatory co-design, and intersectionality-informed approaches. We offer applied guidance on integrating Universal Design and Web Content Accessibility Guidelines (WCAG) principles from the earliest design stages; incorporating assistive technology compatibility; developing accessibility informed user profiles; establishing digital literacy and support pathways; adapting telehealth workflows for diverse needs; and building trust through culturally aligned content. We also outline strategies for equitable design such as embedding disability representation in co-design processes and developing measurement plans that capture accessibility, engagement, and long-term outcomes for people with disabilities. Achieving equitable reach and impact in digital health requires centering disability as a core design and implementation domain. By translating conceptual disability models into concrete design practices, and workflow adaptations, clinicians, researchers, and technology developers can create digital health environments that are more usable, inclusive, and sustainable improving access, experience, and health outcomes for disabled individuals across diverse settings.